ANALYSIS OF PUBLIC PERCEPTION ON X SOCIAL MEDIA REGARDING GOVERNMENT RESPONSE NARRATIVES TO THE 2025 SUMATRA FLOOD AND LANDSLIDE CRISIS - Hayrasyirah Ryazinharwa; Abdul Karim Batubara (Program Pascasarjana UIN Sumatera Utara, 2026)
This study aims to analyze public perception on social media X regarding the narrative of the government's response to the 2025 Sumatra flood and landslide crisis through the perspective of Situational Crisis Communication Theory (SCCT). This study uses a qualitative approach with a content analysis method on 59 public posts consisting of tweets, tweet replies, and tweet quotes during the period of November–December 2025. Data were selected purposively based on relevance to the issue of the government's response, then analyzed through the stages of data reduction, open coding, theme grouping, and theoretical interpretation using SCCT. The results show that public perception is dominated by critical evaluations of the government, especially regarding responses that are considered slow and inadequate, crisis communication that lacks empathy, policy inaccuracy, and the public's tendency to associate disasters with structural issues such as environmental damage and government governance. The findings also show a perception of regional injustice between the central and regional governments, although there is a small amount of support and ambivalent evaluation. From the SCCT perspective, crises that can be objectively categorized as victim crises tend to be perceived by the public as close to preventable crises due to the high attribution of responsibility to the government. This study confirms that social media X plays a crucial role as a digital space in shaping public perceptions, collective emotions, attributions of responsibility, and legitimacy toward government communications in crisis situations.